Analysis of the Level of Community Satisfaction with Police in the Depok Metro Jurisdiction - Lisendra, Multazam; Setyabudi, Chairul Muriman; Darmawan, Roy (GoAcademica Research & Publishing, 2024)
Community satisfaction is an important instrument in determining the success of the police while carrying out their duties, because community satisfaction is a benchmark for police institutions in achieving reflexive and transitive goals. For this reason, this research aims to assess the extent of community satisfaction with the police in the Depok metro jurisdiction. 4 aspects are used to assess the level of public satisfaction with the police, namely aspects of performance effectiveness, procedural justice, police legitimacy and cooperation. This research uses survey techniques and distributes a set of research questionnaires. A descriptive statistical approach was used for data processing and analysis. The results show that the public is satisfied with the performance of the police in the Depok metro jurisdiction. The 4 aspects used to assess the level of community satisfaction showed an average value of 46.5% and 27.5% of respondents felt satisfied and very satisfied with the effectiveness of police performance; 54.6% and 30% of respondents were satisfied and very satisfied with procedural justice; 44% agree, 25.1% disagree with police legitimacy. Meanwhile cooperation or cooperation showed that 64.2% and 29.6% of respondents were satisfied and very satisfied with the model of cooperation with the police.